The role of perceived value in understanding tourist experience and post experience at heritage destinations - Eny Endah Pujiastuti; Adi Soeprapto; Susanta Susanta; Humam Santosa Utomo; Aninda Maharaniputri (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
Purpose: This research aims to develop and test the theoretical model of the use of Means-end theory in the creator of a tourism-coordinated value chain that integrates the concept of memorable tourist experience, perceived value, affective commitment, storytelling behavior and destination loyalty. This study used Means-end theory approach by reviewing perceived value in understanding memorable tourist experience and post-experience behavior (perceived value, tourist satisfaction, affective commitment, storytelling behavior and destination loyalty). In particular, this research examined the influence of variable memorable tourist experience, perceived value, tourist satisfaction, affective commitment, and storytelling behavior on destination loyalty.Design/Methodology/Approach: The population of this research was all tourists who had visited the tourist attraction of Borobudur temple, Magelang Regency, Central Java, Indonesia. The number of samples used was 437 people who were selected with certain considerations, namely tourists who had visited Borobudur Temple at least once. Data collection was carried out in August-October 2020 using google form. This research used SEM analysis tool which was operated by the AMOS application.Finding: The results showed memorable tourist experience that had significant effect on Perceived Value, Storytelling Behavior, Affective Commitment, and Destination Loyalty. Simultaneously, Perceived Value had a significant influence on Storytelling Behavior, Affective Commitment, and Destination Loyalty. Secondly, Storytelling Behavior also had significant effect on Destination Loyalty.Research Limitation/Implications: This research had limitations in sample selection. The sample of this research was tourists who had visited Borobudur temple because the variable used in this research was memorable tourist experience. Ideally, respondents were travelers whose visit time was close to the time of data collection. However, at the time of data collection, the management of Borobudur temple closed tourist access due to the Covid 19 pandemic; thus, the samples used were tourists who had visited Borobudur Temple before the Covid 19 pandemic. Further research is recommended whenever using variable of memorable tourist experience. It is better to use sample of tourists who have visited the destination with a close distance between the visit to the destination and the time of data collection.Practical Implication: The benefits obtained by tourists were illustrated by the perceived value provided by the destination. Therefore, tourism destination managers and marketing staff must focus on the key variable forming perceived value, namely memorable tourism experience. Experience and memorable tourism experience were the main products of the destination. Destination managers and marketers should have a better understanding of tourist needs. They must analyze whether they had created a memorable tourism experience that could create value for tourists.Original Value: The research of the influence of memorable tourist experience, perceived value, tourist satisfaction, affective commitment, and storytelling behavior variable on destination loyalty was the novelty of this research. In addition, the use of the Means-end theory approach to analyze research results was also novelty in this research.